Germline and somatic mutations in cortical malformations: Molecular defects in Argentinean patients with neuronal migration disorders - González Morón, Dolores (2017)
Neuronal migration disorders are a clinically and genetically heterogeneous group of malformations of cortical development, frequently responsible for severe disability. Despite the increasing knowledge of the molecular mechanisms underlying this group of diseases, their genetic diagnosis remains unattainable in a high proportion of cases. Here, we present the results of 38 patients with lissencephaly, periventricular heterotopia and subcortical band heterotopia from Argentina. We performed Sanger and Next Generation Sequencing (NGS) of DCX, FLNA and ARX and searched for copy number variations by MLPA in PAFAH1B1, DCX, POMT1, and POMGNT1. Additionally, somatic mosaicism at 5% or higher was investigated by means of targeted high coverage NGS of DCX, ARX, and PAFAH1B1. Our approach had a diagnostic yield of 36%. Pathogenic or likely pathogenic variants were identified in 14 patients, including 10 germline (five novel) and 4 somatic mutations in FLNA, DCX, ARX and PAFAH1B1 genes. This study represents the largest series of patients comprehensively characterized in our population. Our findings reinforce the importance of somatic mutations in the pathophysiology and diagnosis of neuronal migration disorders and contribute to expand their phenotype-genotype correlations.